Farming the hillsides - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
No one cultivates sloping land out of choice: hillsides are difficult to cultivate, especially with animals or tractors, and they are notoriously prone to water and soil erosion. To reduce or prevent erosion on steep slopes, where simply cultivating...